Evaluation of Awareness and Menstrual Problems Among High School Girls in Rural Areas Linked to a Tertiary Care Hospital - Shubhangi Garg; Anupama Arya; Deepika Anuragi; Garima Solanki; Aesha Zafna; Mohd Adil; Shobhit Saxena; Mugdha M. Mehta (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Adolescent well-being depends heavily on menstrual health, especially for high school girls in rural settings where access to health education and awareness may be restricted. This research assesses high school girls’ knowledge of menstrual hygiene and the frequency of menstruation issues in a rural location near a tertiary care hospital. Materials and Methods: In a rural location, 300 high school girls between the ages of 12 and 18 participated in a cross-sectional research. Their knowledge of common menstruation issues and menstrual hygiene behaviors was evaluated using a standardized questionnaire. Demographic information, knowledge of menstrual health, hygiene habits, and symptoms such as premenstrual syndrome, dysmenorrhea, and menorrhagia were all included in the questionnaire. Descriptive statistics were used to examine the data, and Chi-square tests were used to establish if awareness levels and menstruation issues were related; a P value of less than 0.05 was deemed significant. Results: Of the participants, only 40% had previously received instruction on period health, although 65% were aware of fundamental menstrual hygiene habits. The most frequent menstrual issue mentioned was dysmenorrhea (70%), which was followed by irregular cycles (25%), and menorrhagia (15%). Hygiene behaviors and awareness levels were substantially correlated (P = 0.02). Girls who were more knowledgeable were 50% less likely to report having serious menstruation issues. Conclusion: The research concludes that high school girls in rural regions have a modest understanding of menstrual hygiene and that menstrual issues, especially dysmenorrhea, are rather common. To fill up the information gaps and enhance the well-being of teenage females, educational initiatives centered on menstruation health are crucial.